2017
DOI: 10.1302/2046-3758.65.bjr-2017-0276.r1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic stability over six weeks in aqueous solution at body temperature with and without heat treatment that mimics the curing of bone cement

Abstract: ObjectivesThermal stability is a key property in determining the suitability of an antibiotic agent for local application in the treatment of orthopaedic infections. Despite the fact that long-term therapy is a stated goal of novel local delivery carriers, data describing thermal stability over a long period are scarce, and studies that avoid interference from specific carrier materials are absent from the orthopaedic literature.MethodsIn this study, a total of 38 frequently used antibiotic agents were maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 35 publications
4
69
2
2
Order By: Relevance
“…Fang et al heated metal implants in a rat model to 75 C without any significant thermal damage to the surrounding tissue [31]. These studies are in agreement with Samara et al, who have shown that bone cement achieves durable fixation despite the temperature reaching 80 C for more than 10 min, caused by the curing process of the cement [14]. Furthermore special heating techniques such as segmental induction heating can be used to apply localized heating to a segment of an implant using the remainder of the implant as a heat sink and to avoid damage to vital areas of the implant necessary to maintain fixation [10].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Fang et al heated metal implants in a rat model to 75 C without any significant thermal damage to the surrounding tissue [31]. These studies are in agreement with Samara et al, who have shown that bone cement achieves durable fixation despite the temperature reaching 80 C for more than 10 min, caused by the curing process of the cement [14]. Furthermore special heating techniques such as segmental induction heating can be used to apply localized heating to a segment of an implant using the remainder of the implant as a heat sink and to avoid damage to vital areas of the implant necessary to maintain fixation [10].…”
Section: Discussionsupporting
confidence: 65%
“…There may be concerns for thermal necrosis when heating metal implants to 60-80 C. However, such temperatures are not uncommon in orthopedic surgery with cementing, drilling and using diathermia [11][12][13]. For instance, Samara et al have shown that bone cement, which achieves durable fixation for e.g., hip and knee implants reaches temperatures of 80 C for more than 10 min during the curing process [14]. Additionally, special heating techniques such as segmental induction heating can be used to apply localized heating to a segment of an implant, using the remainder of the implant as a heat sink [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thermogenesis of polymerization: The polymerization of PMMA is an exothermic reaction, [ 36 ] and thus, it is believed that only “heat-stable” antibiotics could tolerate the partial high temperature caused by polymerization. An in vitro test for 38 frequently used antibiotic agents found aminoglycoside, glycopeptide, tetracycline, and quinolone as “heat-stable” and β-lactam as “heat-sensitive.” [ 37 ] Carli et al [ 38 ] conducted thorough research in this field. They measured temperatures of PMMA cured inside silicone molds of the distal femur and proximal tibia and then incubated vancomycin (representing “heat-stable”) and ceftazidime (representing “heat-sensitive”) in accordance with the temperature curves collected from molds.…”
Section: Antibiotic Elution Kinetics Of Albcmentioning
confidence: 99%
“…However, PMMA is not resorbable, implying the disadvantages of incomplete drug release and requirement of secondary removal 2 , 5 - 7 . For many practical and historical reasons, the antibiotics added to PMMA are mostly limited to glycopeptides, such as vancomycin and teicoplanin, aminoglycosides, such as gentamicin or tobramycin, or clindamycin 1 , 4 , 5 , 8 .…”
Section: Introductionmentioning
confidence: 99%